Factors Associated with Skin Cancers in People with Albinism in Togo. (23rd December 2021) - Mouhari-Toure, Abas; Akakpo, Sefako Abla; Teclessou, Julienne Noude; Gnossike, Piham; Adam, Saliou; Mahamadou, Garba; Kassang, Panawé; Elegbede, Yvette; Darre, Tchin; Kombate, Koussake; Pitché, Palokinam; Saka, Bayaki
Abstract : Objective . The aim of this study was to identify the factors associated with skin cancers in people with albinism (PWA) in Togo. Method . This is a retrospective analytical study of the records of PWA examined during five dermatological consultation campaigns from 2019 to 2021. Results . During the study period, 517 PWA were seen. Sixty-four (12.3%) of these PWA had presented with 137 cases of skin cancer. The sex ratio (M/F) was 0.9. The average age of PWA with skin cancer was 39.69 ± 15.61 years and that of PWA without skin cancer was 19.17 ± 15.24 years (p ≤ 0.001 ). The 137 cases of skin cancers were dominated by basal cell carcinomas (45.9%). These skin cancers were located preferentially in the cephalic region (77 cases; 56.2%), followed by the upper limbs (33 cases; 24.1%). In multivariate analysis, the risk factors for skin cancers in PWA were age over 39 years (p ≤ 0.001 ) and the presence of actinic keratoses (p ≤ 0.001 ). In contrast, the presence of ephelides (p = 0.018 ) was a protective factor. Conclusion . This study confirms that advanced age and actinic keratoses are risk factors for skin cancer in PWA, in connection with the cumulative role of solar radiation. Its originality lies in the identification of ephelides as a protective factor. The knowledge and consideration of these risk factors will make it possible to optimise strategies for the prevention of skin cancers in PWA.